African amphorae - (:unkn) unknown (My University, 2019)
In this chapter, we are dealing with containers attributed to Roman Africa, namely the Roman provinces of Mauretania Caesariensis, Numidia and Africa proconsularis, gathered from the beginning of the 4th century onwards into the dioceses of Africa (in the same time as the new provinces of Sitifensis, Byzacena and Tripolitania were cr eated), a nd corresponding to the nowadays (coastal) territories of Algeria and Tunisia, and of the Western part of Libya. Sixty-one sherds of African amphorae have been studied, belonging tothirty different types, and da ted from the mid-2nd century t o t he 7t h c entury AD. A n a ccurate graphic and photographic documentation together with a visual observation of each sherd, followed by a binocular examination of the whole amphora micro-samples, and by a p etrographic an alysis of a s eries of selected thin-sections allowed us to specify the typology and the origin of most of t hese containers . Associated to the chronology and t hecontent hypothesis currently suggested for each of these types, this amphora study sheds new light on the African foodstuff distribution during the Roman and Late Antique times in Northern Adriatic.
Keywords: African Research